Explore the factors that affect on academic performance of female students enrolled in colleges in Southren Punjuab, Pakistan - Sajida Bibi,; Dr. Muhammad Arif,; Dr. Gul Muhammad Shaikh,; Tahira Yasmin,; Sarfraz Hussain,; Muhammad Saqib, (Al-Qanṭara, 2023)
Education has a tremendous impact on life and is essential for the economic prosperity of nations. It nurtures custom, spurs social growth and transformation, leading to widespread reform. Female students from government colleges in Southern Punjab, the study consists of two public sector colleges one is male colleg, Pakistan provided statistical data, which was analyzed using social science metrics to determine the figures. The respondents faced off-campus, economic, social, home-related, college-related issues and teachers related issues that were affecting their educational performance. Falling in love, stress and social status, there were significant factors in the section of Off-Campus issues with values like 2.32, 2.27 and 2.25 respectively. Inflation has been categorized as one of the biggest social issues affecting educational performance. Government should allot a higher budget for public in order to enable this effort. Moreover, refresher courses should be organized for college faculty members to help them equip with the required skills.